VITREOUS INCARCERATION IN SCLEROTOMIES AFTER VALVED 23-, 25-, OR 27-GAUGE AND NONVALVED 23- OR 25-GAUGE MACULAR SURGERY. Issue 10 (October 2017) - Tosi, Gian Marco; Malandrini, Alex; Cevenini, Gabriele; Neri, Giovanni; Marigliani, Davide; Cerruto, Arianna; Virgili, Gianni
Abstract : Purpose: To study the patterns of vitreous incarceration at sclerotomy sites by ultrasound biomicroscopy in patients subjected to valved or nonvalved small-gauge pars plana vitrectomy. Methods: A prospective comparative study of 88 eyes affected by epiretinal membrane and macular hole. Patients were divided into four groups: valved or nonvalved 23-gauge (16 eyes each) and valved or nonvalved 25-gauge (20 eyes each); their vitreal disposition was compared by ultrasound biomicroscopy. Vitreal disposition was also assessed in 16 eyes of 16 patients subjected to valved 27-gauge pars plana vitrectomy. Results: Three vitreal patterns were identified: P0 (vitreous not visible or vitreous strand distant from the sclerotomy site), P1 (vitreous strand parallel to and in contact with the sclerotomy site), and P2 (vitreous strand entrapped in the sclerotomy site). The effect of valved trocar use on vitreous incarceration seemed to be somewhat beneficial, but no statistically significant effect could be shown (odds ratio: 0.85, 95% confidence interval: 0.42–1.74, P = 0.657). Similarly, no differences in vitreous incarceration were shown among vitrectomy gauges (23, 25, or 27) both in a model including valved trocars only ( P = 0.858) and in a model with all available data ( P = 0.935). Conclusion: In 23- and 25-gauge macular surgeries, postoperative vitreous incarceration does not seem to be reduced using valved cannulas and was similar to that observed in 27-gauge surgery. Abstract : Ultrasound biomicroscopy showed no significant differences in perisclerotomy vitreous incarceration patterns between valved and nonvalved 23- and 25-gauge macular surgeries. In addition, no difference in vitreous patterns was present between valved 23, 25, and 27 gauges.